Remagnetization of Carboniferous Limestone in the Zaduo Area, Eastern Qiangtang Terrane, and Its Tectonic Implications - Yu, Liang; Yan, Maodu; Guan, Chong; Li, Bingshuai; Fu, Qiang; Xu, Wanlong; Feng, Zhantao; Zhang, Dawen; Shen, Miaomiao; Xu, Zunbo; Niu, Zhichao (Frontiers in Earth Science, 2022)
Robust paleomagnetic results through geological time are one of the keys to understand the drift history of the Eastern Qiangtang Terrane (EQT). Here we present comprehensive petrographic observations, rock magnetic and paleomagnetic analyses of the early Carboniferous Upper Zaduo (ZD) Limestone Formation (C1z2) from the Sulucun (SLC) section in the Zaduo area, EQT, to investigate its magnetic originality and geological significance. A total of 12 sites (131 samples) were collected. Photomicrograph observations indicate that the limestone samples were characterized by widespread carbonate veinlets. Electron microprobe and energy dispersive spectrometry analyses confirm that authigenic magnetite formed after pyrite. Rock magnetic analyses reveal the dominant magnetic mineral of pyrite and magnetite, with ‘wasp-waisted’ hysteresis loops and close to the ‘remagnetization trend’ hysteresis parameters. Based on both thermal and alternating field demagnetizations, the characteristic remanent magnetization directions for most samples were isolated: Dg=6.3°, Ig=50.1°, kg=54.9, α95=6.2° in-situ, and Ds=330.2°, Is=58.9°, ks=5.9, and α95=20.5° after 2-step tilt correction. The κ (α95) value decreases (increases) after tilt-correction and the ChRM directions failed both the Watson and Enkin (1993) and McFadden (1990) fold tests, indicating post-folding magnetizations. The 11 site-means directions yield a mean in-situ paleopole of 84.4°N, 200.3°E, A95=6.8°, which is coincident with the post ~53 Myr (especially around 40 Ma) paleopoles of the region. We therefore interpret that these early Carboniferous limestone samples contain remagnetized magnetizations and that were obtained after 53 Ma, most likely around 40 Ma, due to the far field effect of the India-Eurasia collision.